Oxytocin and secretin receptors – implications for dry eye syndrome and ocular pain - Lopez, Jacqueline B.; Chang, Chih-Chiun; Kuo, Yien-Ming; Chan, Matilda F.; Winn, Bryan J. (Frontiers in Ophthalmology, 2022)
Dry eye syndrome, a form of ocular surface inflammation, and chronic ocular pain are common conditions impacting activities of daily living and quality of life. Oxytocin and secretin are peptide hormones that have been shown to synergistically reduce inflammation in various tissues and attenuate the pain response at both the neuron and brain level. The oxytocin receptor (OXTR) and secretin receptor (SCTR) have been found in a wide variety of tissues and organs, including the eye. We reviewed the current literature of in vitro experiments, animal models, and human studies that examine the anti-inflammatory and anti-nociceptive roles of oxytocin and secretin. This review provides an overview of the evidence supporting oxytocin and secretin as the basis for novel treatments of dry eye and ocular pain syndromes.